Extracorporeal Membrane Oxygenation for Protected Catheter Ablation in A Post-Cardiotomy Patient With Electrical Storm - Rahul Norawat; Marc O. Maybauer; Niall O’Keeffe; Akbar Vohra (Annals of Cardiac Anaesthesia, 2024)
An electrical storm (ES) refers to multiple occurrences of ventricular arrhythmias within a short time. Catheter ablation is a treatment option for ES but can be challenging in unstable cardiovascular patients. We present the case of a 50-year-old patient with poor left ventricular function who experienced ES after emergency coronary artery bypass grafting (CABG). Despite maximal antiarrhythmic therapy, the patient had recurrent ventricular tachycardia and fibrillation (VT/VF), hindering catheter ablation. Elective venoarterial extracorporeal membrane oxygenation (ECMO) support was established, allowing a successful second catheter ablation attempt without complications. The patient was weaned off ECMO the following day and remained in normal sinus rhythm.